1999
DOI: 10.1007/pl00012378
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Malignant Melanoma in Auckland, New Zealand: Highest Rates in the World

Abstract: The calculation of incidence rates of melanoma in New Zealand has been hampered in the past by incomplete registration of cases. The aim of this study was to document the incidence of melanoma in the Auckland Caucasian population and to define the pathologic characteristics of these lesions. Data were collected for the Auckland region from the New Zealand Cancer Registry and the Auckland Melanoma Unit database for 1995 and combined with census statistics to give the crude and age-standardized rates for invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 20 publications
2
26
1
3
Order By: Relevance
“…Our data indicating that the outcome of patients with regional disease and primary site unknown is similar to patients with regional disease and primary site known when stratified for similar stage of regional disease are in general agreement with the literature (Santini et al, 1985). Local recurrence (LR) in H&NMM has been reported to be more common than for limb melanomas (Douglas & Shaw, 1987;Jones et al, 1999;Ng et al, 2001). Our current findings are in agreement with this in a general sense, with the pie chart summarising the individual main causative factors, namely thickness of the primary, inadequate margin, unfavourable histological sub-type.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our data indicating that the outcome of patients with regional disease and primary site unknown is similar to patients with regional disease and primary site known when stratified for similar stage of regional disease are in general agreement with the literature (Santini et al, 1985). Local recurrence (LR) in H&NMM has been reported to be more common than for limb melanomas (Douglas & Shaw, 1987;Jones et al, 1999;Ng et al, 2001). Our current findings are in agreement with this in a general sense, with the pie chart summarising the individual main causative factors, namely thickness of the primary, inadequate margin, unfavourable histological sub-type.…”
Section: Discussionsupporting
confidence: 89%
“…Further, although H&NMM www.intechopen.com was more common in males the two sites where the incidence was almost the same for males and females (Face and Neck) the outcome was better. We have previously shown that for melanoma overall when all sites are pooled the incidence in males and females is similar (Jones et al, 1999) and that overall males tend to have poorer outcomes than females especially older males (Jones et al, 1999;Shaw, 2008). Trunk and scalp lesions were significantly more common in males in our study: we have previously shown the highest incidence of melanoma in males is on the back (Jones et al, 1999), Scalp melanoma is most common in bald patients and there are more bald men than women (Douglas & Shaw, 1987;Jones et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As the patterns of age-specific incidence rates differ among men and women [1, 9, 10, 17, 23, 29, 34], our results regarding age and sex distribution also correspond well with published data showing higher incidences among young women than among men under the age of 50, but after the age of 60 higher incidences in men than in women [1, 15, 17, 29]. …”
Section: Discussionsupporting
confidence: 81%
“…The percentage of newly diagnosed melanomas that might be missed are reported to be up to 60% (!) in the literature [7, 29, 30]. Basic epidemiologic investigations, like our study, with the data of all centers, diagnosing melanomas histopathologically, and all physicians, critically reviewed by our epidemiologist and our statisticians, may pinpoint the real incidence, almost epidemic.…”
Section: Discussionmentioning
confidence: 99%